Efficacy of a Group Psychoeducation Treatment in Binge Eating Disorder: An Open-Label Study - Liquori, Silvia; Faidutti, Giovanni; Garzitto, Marco; Saetti, Luana; Bendotti, Monica; Balestrieri, Matteo (Frontiers in Psychiatry, 2022)
Aim: To evaluate the efficacy of a group psychoeducation treatment in patients with Binge Eating Disorder (BED). Methods: We designed an open-label efficacy study that included a population of 45 patients diagnosed with BED, who came to our outpatient service and accepted psychoeducation treatment. A measure of eating attitudes and associated psychological constructs was obtained through the use of self-report instruments Eating Disorder Inventory (EDI-3), Binge Eating Scale (BES) and Body Uneasiness Test (BUT). The Symptom Checklist-90 (SCL-90) was also administered to assess general psychopathology. All participants attended 12 weekly group psychoeducation treatment meetings, 8 of which were conducted by a clinical psychologist and a psychiatry resident, and a second module of 4 meetings, oriented towards health and nutrition education topics, conducted by a dietician. Results: At the end of treatment, patients showed significant improvements in body mass index (BMI) and binge eating. Paired t-tests showed significant differences at p-value =.05 in all eating disorder risk scales and for most of the general psychological scales related to eating disorders. In addition, patients experienced an improvement in their perception of overall body image, a decrease in concerns about physical appearance, and less body image avoidance. Finally, results showed that psychoeducation treatment was associated with significant improvements in interpersonal sensitivity. Conclusions: The results of this study may indicate that significant short-term improvements can be achieved through a psychoeducation group for BED patients. Although limited by the lack of a control condition, this study adds to a growing body of evidence with very promising results, laying the groundwork for further case-control studies of BED treatment.